Lifting, Harga Minyak, Cost Recovery dan Pengaruhnya terhadap Dana Bagi Hasil Antara Pemerintah Pusat Dan Daerah Penghasil (Studi pada Industri Migas di Provinsi Riau) - Saleh, Abdul Kadir; Idrus, M. Syafi'i; Salim, Ubud; Setiawan, Margono (Jurnal Aplikasi Manajemen, 2011)
This study is aimed at the analysis of lifting, oil price, fund revitalization, and government revenues, it is also aimed at the analysis on the effect on oil and gas allocation received by the Local Government. Questionnaires were distributed directly to all census elements in the Office of Mining and Energy from a sample of seven regional districts of oil and gas producer areas in the province of Riau. The result of the analysis found that lifting the price of oil and fund revitalization has positive and significant impacts on government revenues. Lifting, oil price, and fund revitalization have both positive and negatif impact on oil and gas product allocation received by Local Government. II, therefore, can be concluded that lifting, oil prices, and fund revitalization potentially have equal proportion to the change of government revenue and product allocation. Meanwhile, changes in government revenue are inversely proportional to changes in fund revitalization. Due to increasing government revenues, the oil and gas producer regions increasingly consider the injustice of fund revitalization revenue.